2016
DOI: 10.1016/j.radcr.2016.08.008
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic resonance imaging of adenoma malignum of the uterine cervix with pathologic correlation: a case report

Abstract: Adenoma malignum (AM) is considered a rare subtype of cervical adenocarcinoma. Although previous reports have described magnetic resonance findings, none of these reports evaluated the utility of diffusion-weighted imaging in the differential diagnosis of AM and other multicystic cervical lesions. We present a case report of an AM that did not show restriction on the apparent diffusion coefficient map, which can be explained by the low cellularity of the tumor. This is consistent with the proper correlation be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
8
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 10 publications
2
8
0
Order By: Relevance
“…19 In contrast, Cast an Senar et al opined that high tumoral ADC values can be explained by low-grade atypia and low mitotic activity as found by histology. 13 Our results are consistent with the former viewpoint. The ROI should be drawn to completely exclude the cystic parts.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…19 In contrast, Cast an Senar et al opined that high tumoral ADC values can be explained by low-grade atypia and low mitotic activity as found by histology. 13 Our results are consistent with the former viewpoint. The ROI should be drawn to completely exclude the cystic parts.…”
Section: Discussionsupporting
confidence: 93%
“…Nougaret et al reported that the solid component was easily detected as an area of high signal intensity with respect to the high‐b‐value image, with corresponding restrictions on the ADC map . In contrast, Castán Senar et al opined that high tumoral ADC values can be explained by low‐grade atypia and low mitotic activity as found by histology . Our results are consistent with the former viewpoint.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Endocervicosis usually does not invade deeply into the cervical stroma and does not contain solid-component enhancement on T2W1-MRI images. In contrast, a multicystic lesion that deeply invades the cervical stroma and contains solid-enhancement portions may indicate a malignant lesion, like carcinoma of the cervix, that usually shows high-signal intensity on T2W1 and post-contrast T1W1 images and low-signal intensity at the cervical stroma on T2 images [ 11 12 ]. In addition, morphologically and radiologically, endocervicosis can mimic adenoma malignum.…”
Section: Discussionmentioning
confidence: 99%